European probation order: What doesn’t work? Recommendations to overcome its underuse - Montero Pérez de Tudela, Esther (Criminology & criminal justice, 2025)
On 28 November 2008, the Council of the European Union (EU) adopted Framework Decision 2008/947/JHA, creating the European Probation Order (EPO). It allows EU citizens sentenced or subject to a probation decision to return to their own countries and implement there the alternative penalty or measure, where competent judicial authorities will supervise the execution of the probation measure. Despite the high number of EU nationals sentenced or punished in EU countries, EPO has been used sparingly. This article examines the obstacles facing its implementation, mainly the lack of knowledge about its utility and other EU probation systems or specific gaps of the norm, and provides proposals for overcoming them, such as more training and promotion of mutual knowledge, a common interpretation to get over the differences among systems and some form of annual monitoring of its use, in order to combat the current situation whereby foreigners are overrepresented in prison.